Nutraceutical quality of Opuntia ficus-indica developed under micro tunnel conditions, applying vermicompost - Reséndez, Alejandro Moreno; Córtes, Dalia Meza; Carrillo, José Luis Reyes; García, Victoria Jared Borroel; Aragón, Mercedes Georgina Ramírez; Rangel, Pablo Preciado; Marszalek, Jolanta Elzbieta (Emirates Journal of Food and Agriculture, 2020)
The demand for Opuntia spp., cladodes has increased substantially due to their low caloric value, high fiber content, their nutritional and functional characteristics and beneficial effects and phytochemical composition. The aim of this work was to determine the content of biochemical components and the antioxidant capacity of the nopal developed under micro tunnel conditions, with VC as a source of fertilization. The plants were grown under micro tunnel conditions with the manual vermicompost application at 15, 30 and 45 t•ha-1. Between February and May 2019, four samplings of three cladodes (12 to 15 cm) from each treatment were obtained. Samples were stored at -20 °C prior to obtaining ethanol extracts. Total phenolic content and total flavonoids were determined using a modification of Folin-Ciocalteu and Zhishen methods, respectively. The ABTS+ test was performed with methodology proposed by Aubad-López. A split plot design, with two replicates, was used. The big plot corresponded to doses of vermicompost and subplots to the three varieties of nopal. Data were statistically analyzed by a two-way ANOVA with repeated measures. Statistical significance was obtained at 95 % confidence level (α = 0.05) using SPSS Statistics. The values recorded for the contents of total phenols, total flavonoids and the antioxidant activity, in the Chicomostoc, Chapingo and Narro varieties suggest that cladodes may be a promising source of natural antioxidants.